PEMBELAJARAN THINK PAIR SHARE BERBASIS CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR - Wulandari, Rizki; Widodo, Antonius Tri (Universitas Negeri Semarang, 2013)
This study was motivated by the lack of student learning outcomes and involvement of the student in class XI of High School in Kudus especially on solubility and solubility results subject. Think pair share learning model based on creative problem solving was applied to overcome these problems. This study aimed to determine the improvement of student learning outcomes. The experiment was conducted on an experimental basis, with the entire population of high school students of class XI. Sampling was done by using cluster random sampling, so then obtained XI IPA 3 class as the experimental class and XI IPA 1 class as the control class. The data of increasing students' cognitive learning outcomes derived from the test multiple choice questions, while the data psychomotor and affective learning outcomes of students were from the observation sheet. The result of data analysis showed an increase in learning outcomes and student activity. In addition, an increase in cognitive learning outcomes classical achieved completeness. It can be concluded that the application of the think pair share learning model based on creative problem solving can improve student learning outcomes.